Women's Empowerment through Umi Shohib's Home Industry Soy Milk Business to Improve the Welfare of Housewives in Deli Tua District, Deli Serdang Regency, North Sumatra - Nurul Adilla Alatas Abus; Yulia Nur Rahmah; Seniati; Berlianti (TALENTA Publisher, 2024)
Gender inequality is a complex problem because it affects an individual's chances of getting a job. It is difficult for women to find work compared to men, making tough and creative women try home industry businesses to continue to carry out their role as housewives. Umi Shobib's soy milk business is an example of a home industry business by women. This business owner has unknowingly empowered women among housewives near his house. This article describes the feasibility of home industry businesses as a form of women's empowerment. The research location is in Deli Tua District, Deli Serdang Regency, North Sumatra. Data collection was carried out through interviews, observation, and documentation. The data was then analyzed using SWOT analysis to see the feasibility of home industry businesses as a form of empowering women and supporting their development. The research results show that empowering women through home industry businesses is quite effective because housewives who find it difficult to find work can increase their independence through working in home industry businesses. The problem experienced by Umi Shohib's soy milk as a home industry business is the lack of knowledge of how to use machines to make soy milk into UHT packaged milk so that it lasts longer. This problem shows that women's empowerment still requires professional experts to act as brokers to help connect clients with professional experts.